Altered natal dispersal at the range periphery: The role of behavior, resources, and maternal condition. Issue 1 (30th November 2016) - Merrick, Melissa J.; Koprowski, John L.
Abstract: Natal dispersal outcomes are an interplay between environmental conditions and individual phenotypes. Peripheral, isolated populations may experience altered environmental conditions and natal dispersal patterns that differ from populations in contiguous landscapes. We document nonphilopatric, sex‐biased natal dispersal in an endangered small mammal, the Mt. Graham red squirrel ( Tamiasciurus hudsonicus grahamensis ), restricted to a single mountain. Other North American red squirrel populations are shown to have sex‐unbiased, philopatric natal dispersal. We ask what environmental and intrinsic factors may be driving this atypical natal dispersal pattern. We test for the influence of proximate factors and ultimate drivers of natal dispersal: habitat fragmentation, local population density, individual behavior traits, inbreeding avoidance, competition for mates, and competition for resources, allowing us to better understand altered natal dispersal patterns at the periphery of a species' range. A juvenile squirrel's body condition and its mother's mass in spring (a reflection of her intrinsic quality and territory quality) contribute to individual behavioral tendencies for movement and exploration. Resources, behavior, and body condition have the strongest influence on natal dispersal distance, but affect males and females differently. Male natal dispersal distance is positively influenced by its mother's spring body mass and individual tendency for movement; female natal dispersal distance is negatively influenced by its mother's spring body mass and positively influenced by individual tendency for movement. An apparent feedback between environmental variables and subsequent juvenile behavioral state contributes to an altered natal dispersal pattern in a peripheral population, highlighting the importance of studying ecological processes at the both range center and periphery of species' distributions. Abstract : Populations at the range periphery may exhibit altered population processes due to differences in density, spatially and temporally heterogeneous resources, and climatic extremes. In contrast to other North American red squirrel populations, natal dispersal in an endemic subspecies at the southern range periphery is sex‐biased with dispersal distances up to nine times greater than observed at the range center. The probability of dispersal and dispersal distance was most influenced by the mass of a juvenile squirrel's mother in spring (a reflection of her intrinsic quality and territory quality) and individual behavioral tendencies for movement and exploration, but these variables influenced males and females differently suggesting a flexible dispersal strategy that may be adaptive in a highly variable environment.